2012
DOI: 10.1016/j.braindev.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute encephalopathy with hemophagocytic lymphohistiocytosis and clonal T-cell expansion

Abstract: We report on a 9-year-old boy who presented with acute encephalopathy and hemophagocytic lymphohistiocytosis (HLH). The patient was referred to our hospital because of fever, seizures, and decreased consciousness. He showed moderately elevated levels of proinflammatory cytokines in the cerebrospinal fluid and plasma, and clonal expansion of highly activated CD8 + T cells in the peripheral blood. These CD8 + T cells were found to be larger cells that stained positive for T-cell receptor V13.6, and decreased sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…6 A case report by Wada et al showed clonal expansion of highly activated CD8þ T-cells in the peripheral blood of HLH patient which decreased after steroid therapy. 7 Another study by Toga et al showed a significant increase in the subpopulation of CD8þ T-cells with CD5 down-regulation in patients with EBV-HLH but not in patients with infectious mononucleosis or in control subjects. 8 These findings suggest a prominent role of CD8þ T-cells in the pathogenesis of HLH.…”
Section: Discussionmentioning
confidence: 97%
“…6 A case report by Wada et al showed clonal expansion of highly activated CD8þ T-cells in the peripheral blood of HLH patient which decreased after steroid therapy. 7 Another study by Toga et al showed a significant increase in the subpopulation of CD8þ T-cells with CD5 down-regulation in patients with EBV-HLH but not in patients with infectious mononucleosis or in control subjects. 8 These findings suggest a prominent role of CD8þ T-cells in the pathogenesis of HLH.…”
Section: Discussionmentioning
confidence: 97%
“…Also, two bone marrow biopsies in the proband did not demonstrate increased hemophagocytosis found in 82% of FHL2 patients. 23 Neurodegeneration has been reported as a possible feature of FHL2 and sporadic HLH, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] with a frequency of 37-69%. 23,29,39,40 A third of patients have neurological symptoms at diagnosis, 40 and 36% of those with PRF1 mutations have some CNS involvement.…”
Section: Discussionmentioning
confidence: 99%